Front Cover: Monocyclometalated (C N) Gold(III) Metallacycles: Tunable Emission and Singlet Oxygen (1O2) Generation Properties (Chem. Eur. J. 58/2021). Issue 58 (8th October 2021) - Malmberg, Robert; Suter, Dominik; Blacque, Olivier; Venkatesan, Koushik
Abstract : A new class of monocyclometalated gold(III) diacetylide metallacycles has been synthesized and characterized. Photophysical investigations of these complexes revealed strong phosphorescence with very long excited‐state lifetimes. We demonstrate the efficient singlet‐oxygen‐generation properties of these metallacycles through their ability to sensitize singlet oxygen. The complexes′ varying ability to generate singlet oxygen opens avenues for their potential use in catalysis and biomedical applications. More information can be found in the Full Paper by K. Venkatesan et al. (DOI: 10.1002/chem.202102331 ).